HAFALAN AL-QUR’AN SISWA PADA MATERI PAI DI SMAN 1 KEC. AKABILURU - Wike Maidi Wita; Arifmiboy Arifmiboy; Junaidi Junaidi; Iswantir Iswantir (Universitas Pahlawan Tuanku Tambusai, 2022)
Researchers conducted research at SMAN 1 Kec. Akabiluru which is motivated by students' problems in memorizing verses of the Qur'an. This research is intended to answer students' problems regarding fluency and fluency in reading students' memorization, the methods used by students in memorizing and also the obstacles faced by students in memorizing the Qur'an Q.S Al-Maidah/5:48 and Q.S At-Taubah/9 :105 on PAI class X material. These problems were investigated using descriptive qualitative research methods. Data was collected by means of observation, interviews, and also documentation. The key informants in this study were students of class X at SMAN 1 Kec. Akabiluru. To analyze the data, the researchers grouped based on the existing problems. The results obtained are, at the level of fluency and fluency of students in memorizing students do not recognize hijaiyah letters and do not understand makharijul letters, but in the law of recitation many are already good even though students do not apply it when depositing memorization. The methods used by students vary, but generally students use the wahdah method, namely by memorizing one verse by one as a whole. Some of the obstacles faced by students come from within and some come from outside. From within him is the student's lack of mastery of the hijaiyah letters, makharijul letters and the law of tajwid, easy to despair, too hasty to memorize. Meanwhile, what comes from the outside is in the form of laziness, lack of concentration, environmental influences, immorality, and others. It can be understood that students are still not fluent and fluent in depositing memorization. The method in memorizing the Qur'an used by students is mostly the wahdah method, which is reading the whole verse over and over without being divided. Constraints faced by students apart from the two descriptions above, there are other things that are inhibiting factors such as lack of focus in memorizing, embarrassed to deposit memorization in front of many people, too many activities, lazy, lack of motivation, environmental influences, being too active in extracurricular activities, easy to drop out hope and so on. Keyword: Memorizing the Qur'an, Islamic Religious Education